A Comparative Experimental Study on Identification of Defect Severity in Rolling Element Bearings using Acoustic Emission and Vibration Analysis - V.V. Rao; Ch. Ratnam (Tribology in Industry, 2015)
This paper describes the comparison between Vibration Analysis (VA) and Acoustic Emission (AE) method to predict the defect severity in rolling element bearings with respect to the gradual increase of defect size. In bearing fault diagnosis vibration based methods are very popular, but the signals acquired by its transducers from the bearings are distorted by other faults and mechanical noise from the equipment. Vibration based methods are effective when the defect in the bearings has already become severe. AE is a non destructive testing (NDT) technique used in structural health monitoring and its application for bearing defect diagnosis is gaining momentum as an alternate diagnostic tool because of its inherent high signal-to-noise-ratio (SNR). A bearing test rig was designed and set up to study the various defects in rolling element bearings in real environment. In earlier cases, though the researchers studied on different types of seeded defects with random sizes, they could not ascertain the correlation between their defect sizes and the vibration amplitude. The experimental investigation reported in this paper is centered on seeded defect of same type with gradual increase of its size on outer race of radially loaded cylindrical roller bearings and running the defective bearing at different speeds and loads. Data acquired through AE & vibration probes simultaneously for better diagnosis. Comparisons between AE and VA over a range of speed and load conditions at gradual increase of defect size are presented and from them it is concluded that AE method is superior to identify the severity of defect.